Psychoses and Epilepsy: Paradoxical Normalization - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Five children aged 2.5 to 9 years who developed paradoxical, or forced normalization (acute psychiatric symptoms with abrupt cessation of seizures and normalized EEG) are reported from the Shaare Zedek Medical Center, Jerusalem.